The two wings of Catholic thought : essays on Fides et ratio - Foster, David Ruel, 1952-; Koterski, Joseph W. (Catholic University of America Press, 2003)
John Paul's choice to yoke faith and reason together in an encyclical on the twin sources of knowledge caught the world's attention. By stressing "the two wings" of Catholic thought, the pope captures in the image of a soaring bird the same point that theologians like von Balthasar communicate by calling truth symphonic. The beauty of this symphony, like the flight of the bird, is even better appreciated when one has studied the component parts. The purpose of this volume is to deepen the appreciation for the stereophonic approach to truth that the Holy Father recommends. The essays are in three sections: (1) doctrinal themes, (2) contemporary implications, and (3) historical aspects. In the first, Avery Cardinal Dulles, S.J., discusses the twentieth-century answers to a question that has long haunted Christians who felt the attraction of pagan philosophy: Can philosophy be Christian? Prudence Allen, R.S.M., and Joseph Koterski, S.J., then treat two philosophical topics that have been the most affected by centuries of contact with the Christian faith: the philosophy of the person and metaphysics. David Meconi, S.J., reflects on the Marian framework that is so typical of Pope John Paul II's thought. In the second section, Bishop Allen Vigneron considers the significance of this encyclical for Catholic intellectual life today. David Foster discusses the implications of Fides et ratio for Catholic universities. In the final section, Koterski reviews the importance of biblical wisdom literature for the encyclical. Michael Sweeney and Timothy Quinn treat medieval philosophy and modern philosophy respectively. Finally Cardinal Dulles considers the Church pronouncements on faith and reason from Vatican I to John Paul II.--Provided by publisher and editors